Market Reaction As An Impact Of The Fed Interest Rate Decrease Announcement In Asian And European Areas - Luh Gede Sri Artini (Matrik : Jurnal Manajemen, Strategi Bisnis, dan Kewirausahaan, 2022)
Market Reaction As An Impact Of The Fed Interest Rate Decrease Announcement In Asian And European Areas ABSTRACT The announcement of the reduction in the Fed's interest rate on July 31, 2019 is a rare event since 2008. The Fed's rate cut will have a major impact on the global economy and conditions in the capital market.The purpose of this study is to determine whether there is a difference in the average abnormal return around the date of the announcement of the Fed's interest rate hike in Asia and the European region. The sample of this study was 18 emerging market countries' index indices in Asia and Europe with sample collection techniques using purposive sampling. This study uses One Way Anova analysis techniques and One Sample T-test. The results found that there was no difference in the average abnormal return before and after the announcement of the Fed's interest rate increase. This condition shows that markets in the two regions do not react significantly because markets in Asia and the European region are in an efficient condition in the form of half strong, where the market absorbs information quickly and is reflected in stock prices so there is no difference in the average abnormal return in both regions. The absence of a difference in the average abnormal return is also caused by the uncertainty of the global economy making investors more careful in making investment decisions.